2017
DOI: 10.4172/2157-7471.1000421
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and Silver Nanoparticles as Control Agents of Some Faba Bean Spot Diseases

Abstract: Faba bean (Vicia fabae L.) is one of the most economic legume crops in Egypt. The antifungal effects of different concentrations of Chitosan and silver nanoparticles (20 ppm, 40 ppm, 60 ppm, 80 ppm and 100 ppm) were studied against aggressive isolates of Botrytis fabae and Alternaria alternata causing chocolate spot disease and Alternaria leaf spot disease respectively. Under laboratory conditions, the application of five concentrations of Chitosan nanoparticles and silver nanoparticles to the cultures of B. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…The results are in corroboration with other studies available on the effects of silver nanoparticles on phytopathogens. The antifungal effects of different concentrations of silver nanoparticles (20 to 100 ppm) were studied against aggressive isolates of Botrytis fabae and Alternaria alternate causing chocolate spot disease and Alternaria leaf spot disease of faba bean [44]. The highest reduction of chocolate spot and Alternaria leaf spot severity was obtained with treatment by 100 ppm of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The results are in corroboration with other studies available on the effects of silver nanoparticles on phytopathogens. The antifungal effects of different concentrations of silver nanoparticles (20 to 100 ppm) were studied against aggressive isolates of Botrytis fabae and Alternaria alternate causing chocolate spot disease and Alternaria leaf spot disease of faba bean [44]. The highest reduction of chocolate spot and Alternaria leaf spot severity was obtained with treatment by 100 ppm of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of germinated spores was counted in microscopic fields that were chosen at random. The percentage of spore germination inhibition (% SGI) was calculated as follows (eq ): % .25em SGI = ( N GS,control N GS,treatment N GS,control ) × 100 …”
Section: Methodsmentioning
confidence: 99%
“…Sharma et al (2012) proved that the inhibitory effects of AgNPs on Sphaerotheca pannosa Var rosae. It can be concluded that the bio-AgNPs had evaluated against phytopathogens (Lamsa et al, 2011;Patel et al, 2014 andAhmed et al, 2017).…”
Section: Antifungal Efficacy Of Agnps Against C Maydismentioning
confidence: 99%